Impact of cytochrome P450 2C19 polymorphisms on the clinical efficacy and safety of voriconazole: an update systematic review and meta-analysis. Issue 7 (21st July 2022) - Zhang, Ying; Hao, Xu; Hou, Kelu; Hu, Lei; Shang, Jingyuan; He, Shiyu; Yang, Changqing; Huang, Lin; Feng, Yufei
Abstract : Objective: To assess the impact of cytochrome P450 (CYP) 2C19 polymorphisms on the clinical efficacy and safety of voriconazole. Methods: We systematically searched PubMed, EMBASE, CENTRAL, ClinicalTrials.gov, and three Chinese databases from their inception to 18 March 2021 using a predefined search algorithm to identify relevant studies. Studies that reported voriconazole-treated patients and information on CYP2C19 polymorphisms were included. The efficacy outcome was success rate. The safety outcomes included overall adverse events, hepatotoxicity, and neurotoxicity. Results: A total of 20 studies were included. Intermediate metabolizers (IMs) and poor metabolizers (PMs) were associated with increased success rates compared with normal metabolizers (NMs) [risk ratio (RR), 1.18; 95% confidence interval (CI), 1.03–1.34; I 2 = 0%; P = 0.02; RR, 1.28; 95% CI, 1.06–1.54; I 2 = 0%; P = 0.01]. PMs were at increased risk of overall adverse events in comparison with NMs and IMs (RR, 2.18; 95% CI, 1.35–3.53; I 2 = 0%; P = 0.001; RR, 1.80; 95% CI, 1.23–2.64; I 2 = 0%; P = 0.003). PMs demonstrated a trend towards an increased incidence of hepatotoxicity when compared with NMs (RR, 1.60; 95% CI, 0.94–2.74; I 2 = 27%; P = 0.08), although there was no statistically significant difference. In addition, there was no significant association between CYP2C19 polymorphisms and neurotoxicity. Conclusion: IMs and PMs were at a significant higher success rate in comparison with NMs. PMs were significantly associated with an increased incidence of all adverse events compared with NMs and IMs. Researches are expected to further confirm these findings. Additionally, the relationship between hepatotoxicity and CYP2C19 polymorphisms deserves clinical attention.